Investigation of Fatal Road Traffic Accidents Involving Passenger Cars Based on Vehicle Age in Hungary - Mészáros, Gábor (Magyar Rendészet, 2025)
Amongst the causes of road traffic accidents, mechanical failure of cars due to their mechanical condition appears with the most minor proportion. Authorities do not examine the possible impacts of the vehicles’ mechanical condition and age on the severity of the road accidents they are involved in. The data on fatal road accidents involving cars will be presented and analysed based on the age composition of the vehicle fleet. The basis of the research is the deep analysis of the concluded investigation documents of fatal road accidents between 2016 and 2017 in all the counties of Hungary since the accident statistics of the Central Statistical Office do not include the data uncovered during the investigation or the accident causes determined at the end of the process. In 2016, the average age of passenger cars was 13.9 years, while the average age of passenger cars involved in accidents where fatalities occurred was 15.5 years. In 2017, the average age of passenger cars was 14.1 years, while the average age of passenger cars involved in accidents was 15.5 years. In cases where another vehicle was involved in the accident, but no one died, the average age of vehicles was 12.1 years in 2016 and 10.9 years in 2017. During accidents, nearly 40% of road users did not use seat belts, which also adversely affected the outcome of the accidents. The ageing of the vehicle fleet harms the severity of accident outcomes, as the passive safety features of more modern vehicles – if used – provide more effective protection for road users.